PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN MEDIA VIDEO TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH IPA PADA SISWA KELAS IV GUGUS 3 KECAMATAN BAJENG KABUPATEN GOWA - Yulpia Samaduri; Ma’ruf; Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the problem-based learning model assisted by video media on students' learning motivation and science problem solving abilities. The type of research used was quasi experimental with a nonequivalent control group design. The population in this study were all class IV students at the Gugus 3 school, Bajeng District, Gowa Regency and the sample was class IV students at SDI Parangrea and SDI Pakingkingan, totaling 43 people. Data collection techniques use questionnaires to determine students' science learning motivation and tests to determine students' science problem solving abilities. The collected data was analyzed quantitatively using descriptive statistics and inferential statistics. The results of descriptive statistical data analysis show that the average score for science learning motivation for the experimental class is 92.83 and for the control class is 51.85. Meanwhile, the average score for science problem solving ability in the experimental class was 86.09 and for the control class was 52.50. Meanwhile, the results of inferential statistical data analysis show that the sig. on learning motivation is 0.000 < 0.05 with a t-count > t-table value, namely 27.670 > 1.681, and the MANOVA test shows a sig. 0.001 < 0.05. Sig value. The problem solving ability is 0.000 < 0.05 with a t-count > t-table value of 9.179 > 1.681. This means that there is an influence of the problem-based learning model assisted by video media on learning motivation and science problem solving abilities in Class IV Cluster 3 Students, District. Bajeng, Gowa Regency